THE IMPORTANCE OF PROPER NUTRITION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE (ResearchJet Journal of Analysis and Inventions, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition characterized by airflow limitation and persistent respiratory symptoms. This article reviews the critical role of proper nutrition in managing COPD, emphasizing the impact of dietary interventions on pulmonary function, inflammation, and overall respiratory health. The literature analysis explores existing studies on the subject, highlighting various methods used to assess the relationship between nutrition and COPD outcomes. The results section summarizes key findings, and the discussion section interprets these results in the context of COPD management. The article concludes with insights into the importance of nutritional support, offering suggestions for incorporating dietary interventions into COPD care.